Develop and test a micropump based on acoustic impedance mismatch - Chew, Eric Rong Jie (Nanyang Technological University, 2022)
This Final Year Project (FYP) report present a study and analysis on impedance pumps based the concept of acoustic impedance mismatch. The project focus on three different pump models, which are two closed loop models and a fluid transfer model. The two closed loop system models are designed to understand the Liebau phenomenon of valveless pumping, its characteristics and the various parameters that affect the flow rate and direction of the fluid in the model. Fluid transfer model is designed and assembled to test for its characteristics.